Notch effect on strength and fatigue life of woven composite laminates - Wan, Ao-Shuang; Xu, Yigeng; Xiong, Junjiang (Elsevier, 2019)
This paper presents an experimental and numerical study of the notch effect on strength and fatigue life of double edge notched (DEN) composite laminates made of woven glass fibre lamina 3238A/EW250F and woven carbon fibre lamina 3238A/CF3052. Experimental results show that the notch effect is dependent on fibre type, notch depth, load type and load sequence. As-n-R-d-r" role="presentation"> s - n - R -d-r residual strength model was proposed to account for the effects of the notch and the stress ratio, and a progressive damage algorithm was developed to predict damage propagation and residual life of composites under spectrum fatigue load. Good agreement between the experimental results and the numerical predictions has been achieved.
Keywords: Notch effect; Woven composite laminates; Fatigue; Block loading; Life prediction